Signal conditioning circuit for gel strain sensors. (25th November 2021) - Payo, Ismael; Polo, José L; López, Blanca; Serrano, Diana; Rodríguez, Antonio M; Antonia Herrero, M; Martín-Pacheco, Ana; Sánchez, Inmaculada; Vázquez, Ester
Abstract: Conductive hydrogels are soft materials which have been used by some researchers as resistive strain sensors in the last years. The electrical resistance change, when the sensor is stretched or compressed, is usually measured by the two-electrode method. This method is not always suitable to measure the electrical resistance of polymers-based materials, like hydrogels, because it could be highly influenced by the electrode/sample interface, as explained in this study. For this reason, a signal conditioning circuit, based on four-electrode impedance measurements, is proposed to measure the electrical resistance change when the gel is stretched or compressed. Experimental results show that the tested gels can be used as resistance force/pressure sensors with a quite linear behaviour.